2017
DOI: 10.1016/j.expneurol.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of brain PPARgamma2 contributes to ketogenic diet anti-seizure efficacy

Abstract: The ketogenic diet (KD) is an effective therapy primarily used in pediatric patients whom are refractory to current anti-seizure medications. The mechanism of the KD is not completely understood, but is thought to involve anti-inflammatory and anti-oxidant processes. The nutritionally-regulated transcription factor peroxisome proliferator activated receptor gamma, PPARγ, regulates genes involved in anti-inflammatory and anti-oxidant pathways. Moreover, endogenous ligands of PPARγ include fatty acids suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 80 publications
5
73
0
1
Order By: Relevance
“…PPARγ is activated by fatty acids, such as decanoic acid, and might therefore mediate anti-inflammatory and anti-oxidant properties of the KD. A PPARγ antagonist abrogated KD-induced seizure protection in Kv1.1 knockout mice, a spontaneously epileptic mouse strain responsive to KD therapy [32], whereas an PPARγ agonist conferred seizure protection; in line with these findings KD therapy was ineffective in preventing seizures in PPARγ knockout mice [33 • ]. Since seizure suppression was associated with a PPARγ induced increase in PPARγ 2 expression, the authors of this study concluded that PPARγ 2 contributes to the anti-seizure effects of KD therapy.…”
Section: Ppars and Inflammatory Pathwaysmentioning
confidence: 97%
“…PPARγ is activated by fatty acids, such as decanoic acid, and might therefore mediate anti-inflammatory and anti-oxidant properties of the KD. A PPARγ antagonist abrogated KD-induced seizure protection in Kv1.1 knockout mice, a spontaneously epileptic mouse strain responsive to KD therapy [32], whereas an PPARγ agonist conferred seizure protection; in line with these findings KD therapy was ineffective in preventing seizures in PPARγ knockout mice [33 • ]. Since seizure suppression was associated with a PPARγ induced increase in PPARγ 2 expression, the authors of this study concluded that PPARγ 2 contributes to the anti-seizure effects of KD therapy.…”
Section: Ppars and Inflammatory Pathwaysmentioning
confidence: 97%
“…Our previous study indicated that the KD and pioglitazone share a mechanism of action via the transcription factor PPARγ 4 . Therefore, we hypothesized that co-administration of a KD and pioglitazone would have additive effects.…”
Section: Resultsmentioning
confidence: 99%
“…The KD has been demonstrated to have consistent effects across laboratories on seizure threshold in the flurothyl model of acutely provoked generalized clonic and tonic-clonic seizures 4,13,14 ; thus, this model was chosen to test our hypothesis. Before performing co-administration studies, it was necessary to determine both effective and ineffective KD ratios against flurothyl-induced clonic and GTC seizures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations